Utopía y ratio gubernatoria en la conquista de América - Mora Rodríguez, Luis Adrián (2013)
In this paper, we propose a new approach to the political and philosophical analysis of the conquest of America. We take the concept of ratio gubernatoria that Michel Foucault uses to describe the deployment of modernity, and we use it to analyse the Memoriales de Remedios written by Bartolomé de Las Casas between 1516 and 1518.